Factors associated with early 14-day unplanned hospital readmission: a matched case-control study - Yu-Tai Lo; Chia-Ming Chang; Mei-Hua Chen; Fang-Wen Hu; Feng-Hwa Lu (BMC, 2021)
Abstract Background/Purpose Early unplanned hospital readmissions are burdensome health care events and indicate low care quality. Identifying at-risk patients enables timely intervention. This study identified predictors for 14-day unplanned readmission. Methods We conducted a retrospective, matched, case-control study between September 1, 2018, and August 31, 2019, in an 1193-bed university hospital. Adult patients aged ≥ 20 years and readmitted for the same or related diagnosis within 14 days of discharge after initial admission (index admission) were included as cases. Cases were 1:1 matched for the disease-related group at index admission, age, and discharge date to controls. Variables were extracted from the hospital's electronic health records. Results In total, 300 cases and 300 controls were analyzed. Six factors were independently associated with unplanned readmission within 14 days: previous admissions within 6 months (OR = 3.09; 95 % CI = 1.79-5.34, p < 0.001), number of diagnoses in the past year (OR = 1.07; 95 % CI = 1.01-1.13, p = 0.019), Malnutrition Universal Screening Tool score (OR = 1.46; 95 % CI = 1.04-2.05, p = 0.03), systolic blood pressure (OR = 0.98; 95 % CI = 0.97-0.99, p = 0.01) and ear temperature within 24 h before discharge (OR = 2.49; 95 % CI = 1.34-4.64, p = 0.004), and discharge with a nasogastric tube (OR = 0.13; 95 % CI = 0.03-0.60, p = 0.009). Conclusions Factors presented at admission (frequent prior hospitalizations, multimorbidity, and malnutrition) along with factors presented at discharge (clinical instability and the absence of a nasogastric tube) were associated with increased risk of early 14-day unplanned readmission.